PENGUATAN WAWASAN HUKUM BAGI KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN - Daud Rismana; Ninik Zakiyah; Heni Kusuma; Alimaskur (Ikatan Dosen Menulis, 2023)
COVID-19 pandemic is a global epidemic that attacks even remote villages, including targeting families who are beneficiaries of the family program of hope. The impacts experienced are varied, and what is definitely unavoidable is the economic sector. As a result of this, the government did not remain silent and moved quickly by issuing policies related to the priority of using village funds in 2020 to deal with the COVID-19 pandemic that occurred in villages. However, in practice, it turned out that it was still not optimal due to a lack of understanding of the existing regulations, so that it had created a commotion in the community. The lack of understanding of the policy is due to the lack of legal insight for the beneficiary families of the family of hope program. So if it is allowed to continue, the law that is born does not create order in society, but becomes a trigger for the rift of harmony in society. The methods used in this community service activity are the lecture method, the discussion method, and the evaluation method. This activity to strengthen legal insight resulted in the first conclusion, this activity is very necessary and beneficial for PKH beneficiary families in Gedangan Village, Wirosari District. Second, increasing legal insight into regulations regarding the priority use of village funds in 2020. The third is that not all KPM PKH in Gedangan Village, Wirosari District have the opportunity to participate in this activity due to a very limited budget.